Age-Induced Loss of Mossy Fibre Synapses on CA3 Thorns in the CA3 Stratum Lucidum. (24th June 2013) - Ojo, Bunmi; Davies, Heather; Rezaie, Payam; Gabbott, Paul; Colyer, Francis; Kraev, Igor; Stewart, Michael G.
Abstract : Advanced ageing is associated with hippocampal deterioration and mild cognitive decline. The hippocampal subregion CA3 stratum lucidum (CA3-SL) receives neuronal inputs from the giant mossy fibre boutons of the dentate gyrus, but relatively little is known about the integrity of this synaptic connection with ageing. Using serial electron microscopy and unbiased stereology, we examined age-related changes in mossy fibre synapses on CA3 thorny excrescences within the CA3-SL of young adults (4-month-old), middle-aged (12-month-old), and old-aged (28-month-old) Wistar rats. Our data show that while there is an increase in CA3 volume with ageing, there is a significant (40–45%) reduction in synaptic density within the CA3-SL of 12- and 28-month-old animals compared with 4-month-old animals. We also present preliminary data showing that the CA3 neuropil in advanced ageing was conspicuously full of lipofuscin and phagolysosome positive, activated microglial cellular processes, and altered perivascular pathology. These data suggest that synaptic density in the CA3-SL is significantly impaired in ageing, accompanied by underlying prominent ultrastructural glial and microvascular changes.